2022
DOI: 10.3390/diagnostics12081800
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Febrile Neutropenia in Pediatric Oncology Patients—A Systematic Review

Abstract: Infectious diseases are associated with a high morbidity and mortality rate among pediatric cancer patients undergoing treatment or receiving a transplant. Neutropenia represents a potentially fatal complication of cancer treatment and is associated with a high risk of developing bacterial infections. Although febrile neutropenia (FN) can affect both adults and children, the latter has a higher chance of infections with an unknown origin. Prompt empiric broad-spectrum antibiotic administration is collectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…21 Empiric antibiotics are required for severely neutropenic patients with fever because of their risk for severe bacterial infection and the inability to distinguish which patients have a bacterial etiology at fever presentation. 1,2 There exists a small subset of patients with FN who have severe sepsis at presentation for whom quick action is always needed (0.6% of episodes in this cohort). For these patients, antibiotics must be given urgently as this study showed a mortality rate over 57% even when antibiotics were given rapidly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Empiric antibiotics are required for severely neutropenic patients with fever because of their risk for severe bacterial infection and the inability to distinguish which patients have a bacterial etiology at fever presentation. 1,2 There exists a small subset of patients with FN who have severe sepsis at presentation for whom quick action is always needed (0.6% of episodes in this cohort). For these patients, antibiotics must be given urgently as this study showed a mortality rate over 57% even when antibiotics were given rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Febrile neutropenia (FN) during pediatric cancer therapy can be a life-threatening emergency 1-3 and is also a leading cause of hospital admission. 2,4 Patients are instructed to seek immediate medical evaluation with fever onset, and standard practice mandates empiric intravenous (IV) antibiotics in those who are severely neutropenic (absolute neutrophil count [ANC] <500 cells/µL 1 ). Time to antibiotic (TTA) refers to the time from patient arrival at a medical center until the time when empiric parenteral antibiotics are administered.…”
Section: Introductionmentioning
confidence: 99%
“…FN patients with weakened immune systems are particularly vulnerable to fungal and viral infections. Without available evidence, fungi and viruses are rarely identified as the cause of early fever in FN ( Boeriu et al., 2022 ). Traditional methods for detecting fungal and viral infections are limited and often lead to missed diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of Gram-negative bacteria are considered to be pathogens. Distinguished by their unique cell envelope structure, Gram-negative bacteria are associated with a higher mortality and morbidity rate on a global scale [ 4 , 5 , 6 ]. On the other side, many different Gram-positive bacteria are commonly known for some of the most dangerous community and healthcare-associated resistant infections [ 7 ].…”
Section: Introductionmentioning
confidence: 99%